2010
DOI: 10.1038/ajg.2010.151
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Eosinophils and CCR2-/CD68-Double Positive Cells Into the Duodenal Mucosa of Patients With Postinfectious Functional Dyspepsia

Abstract: Migration of inflammatory cells, in particular, duodenal CCR2-positive macrophages, may have an important function in the pathophysiology of postinfectious FD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
3
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 34 publications
7
90
3
5
Order By: Relevance
“…A recent study found the degree of histological duodenitis in bacterial postinfectious dyspepsia to be signifi cantly higher than that found in healthy volunteers and correlate with epigastric burning; however, no correlation was found with gastric emptying values ( 34 ). Th ese authors also observed that CCR2-positive macrophage and eosinophil counts were signifi cantly increased.…”
Section: Pathophysiology Of Postinfectious Dyspepsiasupporting
confidence: 60%
“…A recent study found the degree of histological duodenitis in bacterial postinfectious dyspepsia to be signifi cantly higher than that found in healthy volunteers and correlate with epigastric burning; however, no correlation was found with gastric emptying values ( 34 ). Th ese authors also observed that CCR2-positive macrophage and eosinophil counts were signifi cantly increased.…”
Section: Pathophysiology Of Postinfectious Dyspepsiasupporting
confidence: 60%
“…pylori-related dyspepsia is considered a separate entity. However, other prior gastrointestinal infections have been described as triggers of functional dyspepsia, by impairing gastric accommodation (a vagally mediated reflex that occurs postprandially and results in a reduction of smooth muscle tone; the stomach relaxes and provides a reservoir for the meal), possibly via immune mechanisms [51][52][53] .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…The most widely used generic measure, the Short Form 36-Item Health Survey (SF-36) 222 , assesses eight dimensions of health: physical functioning, social functioning, Nature Reviews | Disease Primers Fatty foods , milk and dairy Alcohol , coffee Red meat Carbonated drinks Vegetables Spicy foods Carbohydrates and wheat (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) Citrus (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) Figure 5 | Foods and food groups frequently associated with symptom induction or exacerbation in functional dyspepsia. Offending foods reported by patients with functional dyspepsia include fatty food (for example, fried food [179][180][181]187,191 ), alcohol 179,180 , dairy products 179,181 , coffee [179]…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Comment: In some cases of infectious gastroenteritis accompanied by fever, diarrhea, nausea, vomiting, and positive stool culture, studies have shown that FD symptoms persist long after the elimination of the causative pathogens [32,33]. Postinfectious FD is associated with early satiety, weight loss, and nausea [34].…”
Section: Postinfectious Fdmentioning
confidence: 99%